1991
DOI: 10.1002/j.1460-2075.1991.tb07847.x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional activation by heterodimers of the achaete-scute and daughterless gene products of Drosophila.

Abstract: The achaete‐scute complex (AS‐C) and the daughterless (da) genes encode helix‐loop‐helix proteins which have been shown to interact in vivo and to be required for neurogenesis. We show in vitro that heterodimers of three AS‐C products with DA bind DNA strongly, whereas DA homodimers bind weakly and homo or heterocombinations of AS‐C products not at all. Proteins unable to dimerize did not bind DNA. Target sequences for the heterodimers were found in the promoters of the hunchback and the achaete genes. Using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
157
0
6

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(173 citation statements)
references
References 72 publications
9
157
0
6
Order By: Relevance
“…da genetically interacts with ato da is a known positive regulator of the AS-C genes and encodes a bHLH protein (Caudy et al 1988). The 'active' heterodimers between Da and AS-C proteins have been shown to promote the development of mechanosensory bristles (Cabrera & Alonso 1991). Da is known to form in vitro complexes with Ato which are capable of binding to the E-boxes of DNA (Jarman 1993).…”
Section: Ato Expresses In the Developing Antennal Discmentioning
confidence: 99%
See 1 more Smart Citation
“…da genetically interacts with ato da is a known positive regulator of the AS-C genes and encodes a bHLH protein (Caudy et al 1988). The 'active' heterodimers between Da and AS-C proteins have been shown to promote the development of mechanosensory bristles (Cabrera & Alonso 1991). Da is known to form in vitro complexes with Ato which are capable of binding to the E-boxes of DNA (Jarman 1993).…”
Section: Ato Expresses In the Developing Antennal Discmentioning
confidence: 99%
“…A failure in this process results in the specification of multiple SOPs and hence ectopic sense organs. Genetic and molecular studies have shown that the AS-C gene products are positively regulated by daughterless (da) (Cabrera & Alonso 1991) and negatively by extramacrochaetae (emc) (Ellis et al 1990;Garrell & Modolell 1990) and hairy (h) (Ohsako et al 1994;Van Doren et al 1994). In the case of mechanosensory bristles, once selected, an SOP undergoes two rounds of cell division to give rise to four cells which in turn differentiate to form one neuron and three support cells, the trichogen (shaft), the tormogen (socket) and the thecogen (sheath) .…”
Section: Introductionmentioning
confidence: 99%
“…Their expression determines the position, timing and extent of neural stem cell selection as well as the identity of the neural cells in each lineage. These proteins, which are known as proneural proteins, promote NPC formation by forming heterodimers with a widely expressed bHLH protein, called Daughterless (DA) in Drosophila (Cabrera and Alonso, 1991), and E12/E47 in vertebrates (Murre et al, 1989). The proneural-DA heterodimer regulates transcription of target genes by binding, via some of the residues in the two basic domains, to a DNA motif called the E-box.…”
Section: Introductionmentioning
confidence: 99%
“…The Ac and Sc proteins share 70% identity in their bHLH domains (3), and form heterodimers with the ubiquitously expressed bHLH protein Daughterless (Da) to activate transcription of downstream target genes (13,14). One target gene of Ac and Sc, asense (ase), also encodes a bHLH protein that is specifically expressed in SOPs and involved in SOP differentiation (15-17).…”
mentioning
confidence: 99%